PENGARUH PENGELOLAAN MODAL KERJA TERHADAP PROFITABILITAS DAN LIKUIDITAS DENGAN SIKLUS BISNIS SEBAGAI VARIABEL MODERASI - Dian Ratnasari Yahya (STIE Mahardhika, 2019)
This study aims to examine and analyze the effect of working capital management on profitability and liquidity with the business cycle as a moderating variable. The research is quantitative by using secondary data in the form of financial statements, the population used is a manufacturing company with a sample of 81 companies from 2005 to 2015. Data management has done by using SPSS (Statistical Program for Social Science). The results reveal that inventory turnover has no significant effect on profitability, accounts receivable turnover and debt turnover has significant negative effect on profitability, so the cash conversion cycle negatively does not give an affect of profitability due to business cycle conditions that fluctuated from 2005 to 2015. Inventory turnover, accounts receivable turnover, debt turnover and cash conversion cycle have significant negative effect on liquidity. Business cycles (D1) and (D2) are moderate management of working capital towards profitability. The business cycle (D1) is moderates the management of working capital towards liquidity and the business cycle (D2) is not moderate the management of working capital towards liquidity.